IMPACT OF PREDICTIVE ANALYTICS ON THE ACTIVITIES OF COMPANIES - A. R. Khasanov (Real Economics Publishing House, 2018)
To analyze the impact of predictive analytics on the activities of companies the research was conducted. Subject information: analytics, diagnostics, predicative analytics. The main tools of predictive analytics and solutions in the market of technical solutions are considered. Thanks to the tools of predictive analytics, companies can analyze and predict the processes that occur in time, identify trends, anticipate changes and, for example, plan future more effectively.